Effect of Dietary Lipid Levels on Growth and Survival of Fingerlings of the Indian Major Carp Cirrhinus mrigala - K., Marimuthu; N., Sukumaran (Fishery Technology, 2025)
Six isonitrogenous semi purified diets with graded levels of lipids (4.5, 6, 7.5, 9, 10.5 and 12%) were prepared in pelleted form and fed to the fingerlings of Cirrhinus mrigala for 60 days to evaluate the changes in growth and feed conversion. Absolute, relative and specific growth rates were found to be higher and FCR values better in fishes receiving a diet containing 7.5% lipid